Comprehensive review of carbon quantification by improved forest management offset protocols - Haya, Barbara K.; Evans, Samuel; Brown, Letty; Bukoski, Jacob; Butsic, Van; Cabiyo, Bodie; Jacobson, Rory; Kerr, Amber; Potts, Matthew; Sanchez, Daniel L. (Frontiers in Forests and Global Change, 2023)
Improved forest management (IFM) has the potential to remove and store large quantities of carbon from the atmosphere. Around the world, 293 IFM offset projects have produced 11% of offset credits by voluntary offset registries to date, channeling substantial climate mitigation funds into forest management projects. This paper summarizes the state of the scientific literature for key carbon offset quality criteria—additionality, baselines, leakage, durability, and forest carbon accounting—and discusses how well currently used IFM protocols align with this literature. Our analysis identifies important areas where the protocols deviate from scientific understanding related to baselines, leakage, risk of reversal, and the accounting of carbon in forests and harvested wood products, risking significant over-estimation of carbon offset credits. We recommend specific improvements to the protocols that would likely result in more accurate estimates of program impact, and identify areas in need of more research. Most importantly, more conservative baselines can substantially reduce, but not resolve, over-crediting risk from multiple factors.